Numerical simulations of flow around two tandem wall-mounted structures at high Reynolds numbers. (June 2020) - Yin, Guang; Andersen, Martin; Ong, Muk Chen
Highlights: 2D numerical simulations of the flow around two square and trapezoidal wall-mounted structures in tandem are carried out. The effects of the incline angle of two side slopes of the wall-mounted structures on the hydrodynamic quantities are studied. The effects of the gap ratio between the two structures on the hydrodynamic quantities are studied. Abstract: In the present study, the flow around two-dimensional (2D) square and trapezoidal wall- mounted structures in tandem on a horizontal flat wall has been simulated using two-dimensional Reynolds-averaged Navier-Stokes (RANS) equations combined with the standard k − ω SST turbulence model. The Reynolds number ( Re ) based on the free stream velocity and the height of the structures is set to be 1.19 × 10 5 . The effects of the gap ratio between the two structures as well as the slope angles of the two sides of the trapezoidal structures on the hydrodynamic quantities and the flow around the two structures have been investigated and discussed.